Biology for matriculation - Lee, Soon Ching; Sudani Sudin; Nalini B.; Jacqueline R.S (Oxford Fajar Sdn Bhd, 2015)
Biology for Matriculation Semester 2 Fourth Edition Updated is a comprehensive coursebook written for students studying Biology in local matriculation colleges. It is based on the Matriculation Biology SB026 syllabus issued by the Matriculation Division, Ministry of Education, Malaysia. This coursebook aims to stimulate students' interest in biology and help them gain a firm understanding of important principles and concepts in biology. In addition, it helps students prepare for their Biology examination.